Fatigue strength of SS400 steel under non-proportional loading - T. Morishita; T. Takaoka; T. Itoh (Fracture and Structural Integrity)
This study discusses fatigue properties of low carbon steel, type SS400 steel, under non-proportional loading. Multiaxial fatigue tests under proportional and non-proportional loading conditions with various stress amplitudes were carried out using a hollow cylinder specimen at room temperature. In the test, three types of stress paths were employed. They are a push-pull, a reversed torsion and a circle loading. The circle loading is a cyclic loading combined the push-pull and the reversed torsion loading in which axial and shear stress waveforms have 90 degrees phase differences. From the obtained test results, poor evaluations of failure life under non-proportional loading are indicated when the life is correlated by the equivalent strain range based on von Mises ??eq and the non-proportional strain range ??NP. A modified strain parameter is presented which can evaluate the failure life in high and low strain levels under non-proportional loading.